2018
DOI: 10.1016/j.biopha.2018.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the protective effects of melatonin on di(2-ethylhexyl) phthalate-induced testicular injury in adult mice

Abstract: Melatonin considerably inhibits DEHP-induced gonadotoxicity through reducing oxidative stress and inflammatory responses. These results suggest that melatonin may be considered as a promising agent to reduce toxic effects of endocrine disrupting chemicals such as DEHP on the male reproductive system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 81 publications
5
28
0
3
Order By: Relevance
“…In addition, our results showed that treatment of cells with DEHP induced over generation of intracellular ROS that leads to a disturbance of redox status balance in cells. In agreement with our studies, a significant increase in ROS generation was observed in vivo and in vitro studies following DEHP treatment . ROS overproduction observed in this work is an index of oxidative stress installation that could be the result of the antioxidant system incapacity to neutralize the ROS overproduction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, our results showed that treatment of cells with DEHP induced over generation of intracellular ROS that leads to a disturbance of redox status balance in cells. In agreement with our studies, a significant increase in ROS generation was observed in vivo and in vitro studies following DEHP treatment . ROS overproduction observed in this work is an index of oxidative stress installation that could be the result of the antioxidant system incapacity to neutralize the ROS overproduction.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, in the present study, the MTT assay indicated that Abbreviations: GAPDH, glyceraldehyde 3-phosphate dehydrogenase; HO-1, heme oxygenase-1; Nrf2, NF-E2 related factor 2. significant increase in ROS generation was observed in vivo and in vitro studies following DEHP treatment. [44][45][46] ROS overproduction observed in this work is an index of oxidative stress installation that could be the result of the antioxidant system incapacity to neutralize the ROS overproduction. In our study, compared with those of the control group, the activities of SOD and CAT increased significantly in DEHP treated cells.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, these increases were insufficient to protect the liver from free radicals. In agreement with our studies, a significant increase in oxidative stress generation was observed in vivo and in vitro studies following DEHP treatment …”
Section: Discussionsupporting
confidence: 93%
“…The finding that melatonin counteracted the actions of DEHP on the ovaries caused by the pollutant is in line with several other studies indicating that melatonin protects a variety of organs and cell types including adult testes and ovaries and sperm and oocytes against phthalate toxicity. 49,50 Melatonin exerts its effect through its receptors and in this regard. We report here that oocytes express significant level of MT1 receptor and the addition of DEHP promoted the expression of MT1.…”
Section: Discussionmentioning
confidence: 99%